2009
DOI: 10.1111/j.1469-8986.2009.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced event‐related low frequency EEG activity in schizophrenia during an auditory oddball task

Abstract: This study examines EEG low frequency characteristics which have been linked to specific cognitive functions such as stimulus encoding and attention during an auditory oddball task in schizophrenia patients and healthy controls. EEG data was recorded from 17 young schizophrenia patients in a stable phase of their illness and 17 healthy controls performing an auditory oddball task. Evoked and induced delta and theta activity, N100, P300 amplitude were computed. Between 200-500 ms after a stimulus was presented,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 74 publications
7
39
1
1
Order By: Relevance
“…Fast oscillations may contribute to forming local neuronal assemblies [38], which, according to our results, may suggest a relative deficit in the integration of activities from distant regions in schizophrenia. Relative power reductions in the slower bands were also noted, in accordance with previous data [39]. …”
Section: Discussionsupporting
confidence: 80%
“…Fast oscillations may contribute to forming local neuronal assemblies [38], which, according to our results, may suggest a relative deficit in the integration of activities from distant regions in schizophrenia. Relative power reductions in the slower bands were also noted, in accordance with previous data [39]. …”
Section: Discussionsupporting
confidence: 80%
“…Specifically, in line with Shin et al (2010), we did not replicate the results concerning the dependence of P300 amplitude and gamma band activity in controls reported by Ford et al (2008). We replicated the association between lower values for P300 and lower synchrony on the delta and theta bands (Doege et al, 2009;Ergen et al, 2008;Ford et al, 2008). However, we have shown that these reductions are only present in patients with abnormal P300 amplitudes and are also manifest in control participants without schizophrenia with lower P300 values.…”
Section: Discussioncontrasting
confidence: 48%
“…Frequency domain analyses of EEG activity during oddball tasks have revealed that patients with schizophrenia present reduced amplification of delta activity during target and non-target processing (Röschke and Fell, 1997), reduced evoked and induced delta activity to both target and non-target trials, and a reduced augmentation of evoked and induced theta to targets relative to non-targets on the 200-500 ms time window (Doege et al, 2009). P300 reductions may further be explained by a difficulty in synchronizing post-stimulus delta activity in patients with schizophrenia, as revealed by lower values of Inter-Trial Phase Coherence (Doege et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This failure to modify prior belief in the presence of new evidence is supported by an extensive literature demonstrating this for example, in visual processing of hollow mask illusions (Schneider et al , 2002), and their neural correlates (Dima et al , 2009). Other modalities such as event related potentials in processing discrepant information (Debruille et al , 2007), impaired stimulus evaluation (Doege et al , 2009) and our own work on predictive models distinguishing self and other (Shergill et al , 2005; Simons et al 2010) suggest that top-down modulation in the integration of evidence is dysfunctional in schizophrenia.…”
Section: Discussionmentioning
confidence: 98%